Self Reward Dalam Meningkatkan Motivasi Belajar di Pondok Pesantren Mahasiswa Annidhom Kota Cirebon - Maslinda Hudaifatusaniyah; Septi Gumiandri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Education in general consists of two types: formal and non-formal education. However, some parents choose to provide both forms of education simultaneously, such as in the case of mahasantri (student-santri) at the An-Nidhom Islamic Boarding School. These students bear the responsibility of formal academic learning at their university, which includes numerous courses and assignments, while also being responsible for religious studies at the pesantren, including memorization and various lessons. This raises the question of how mahasantri at the An-Nidhom Islamic Boarding School maintain their learning motivation through self-reward and how they enhance their motivation. This study aims to examine the influence of self-reward on the learning motivation of university students at An-Nidhom Islamic Boarding School in Cirebon City, in terms of both its maintenance and improvement, using Fredrick Herzberg’s motivation theory. This research is a field study using a descriptive qualitative method.. The conclusion of this study is that the mahasantri at An-Nidhom Islamic Boarding School demonstrate a balanced and ideal level of motivation, as evidenced by the fulfillment of the two factors in Fredrick Herzberg’s motivation theory: the hygiene factors and the motivation factors. The alignment of efforts between the pesantren and the mahasantri results in both the maintenance and enhancement of the students’ learning motivation. A strong and systematic collaboration in providing appreciation and motivation ensures that learning objectives are successfully achieved.